ASSESSING EDUCATIONAL MANAGEMENT PRACTICES AT ZION SENIOR HIGH SCHOOL, MAKASSAR USING THE CIPPO FRAMEWORK - Demitrius Jonathan; Arismunandar Arismunandar; Muh. Ardiansyah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the educational management of SMA Zion Makassar using the CIPPO evaluation model (Context, Input, Process, Product, Outcome). The model was chosen because it provides a comprehensive framework for assessing the effectiveness of school management from planning and implementation to outcomes and long-term impacts on students and society. The study employed a qualitative descriptive method with data obtained through observation, interviews, and document analysis. The results indicate that in terms of context, SMA Zion Makassar possesses a strong vision and mission emphasizing Christian character formation and global competitiveness, supported by high community interest and parental involvement. Regarding input, the school’s human resources and facilities are adequate, although several teachers have not yet obtained professional certification. The process dimension shows well-structured learning activities with regular supervision and evaluation, beginning with daily worship as a distinctive feature of the institution. The product dimension reflects competitive academic and non-academic achievements, while the outcome dimension demonstrates that many graduates pursue higher education both domestically and abroad. The study concludes that SMA Zion Makassar has implemented effective educational management, yet further improvement is required in teacher professional development and diversification of funding sources